Bone by bone a novel - Matthiessen, Peter (New York : Recorded Books, 2009)
This is the conclusion and capstone to Matthiessen's remarkable trilogy about the mysterious E.J. Watson, which began with Killing Mr. Watson (1991) and continued with Lost Man's River (1997). In those novels, the sons of the legendary southwest Florida entrepreneur and outlaw were engaged, at a time closer to our own, in digging out the man's story, trying to separate certifiable fact from the miasma of gossip and legend. This time, Matthiessen has given us Watson's own story in Watson's own words, and it is a book of heroic, even tragic, proportions. That story goes right back to Civil War days in South Carolina, and the terrible childhood E.J. endured at the hands of his drunken, brutal and rascally father and his remote and vindictive mother. Thus were laid the seeds of the later outbursts of violence and rage that so frequently punctuated what should have been a promising life. For Watson, as he portrays himself, is ambitious, hardworking and ever ingenious at figuring ways to make the remote Florida Everglades shores yield richesAa true pioneer spirit. He also makes clear, however, the fearful price paid for the development of wild America, not only the despoilation of the hauntingly evoked natural beauty but also the brutal disregard of any kind of human rights among the poor blacks and chain gang prisoners who bore the brunt of the exploiters' drive for wealth and power. Seldom has the profound and unthinking racism of the time (the narrative spans roughly 1860-1910) been so unsparingly presented. The narrative, though long and crowded with often bewilderingly interrelated characters, is also packed with dramatic action: many murders (including that of the legendary Belle Starr, when E.J. is temporarily resident in Indian Territory), ambushes, lynchings, drownings, jailings, a trial and a spectacular hurricane. Always Watson is striving for the respectability of wealth, always he is brought down by the conniving of his kinfolk, his tempers, his love of strong drink and his tormented inability to tolerate the lying and hypocrisy he finds everywhere around him. He is a monumental creation, and in bringing him and his amazing period to life with such vigor Matthiessen has created an unforgettable slice of deeply true and resonant American history.
Sequal to: Killing Mister Watson and Lost Man's River.
Maps on lining papers.
Keywords: Watson, Edgar J., -- 1855-1910 -- Fiction; Frontier and pioneer life -- Fiction; Sugarcane -- Fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction; Historical fiction; Biographical fiction